2002
DOI: 10.1128/aem.68.5.2269-2277.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tract Location of Escherichia coli O157:H7 in Ruminants

Abstract: Experimentally inoculated sheep and cattle were used as models of natural ruminant infection to investigate the pattern of Escherichia coli O157:H7 shedding and gastrointestinal tract (GIT) location. Eighteen forage-fed cattle were orally inoculated with E. coli O157:H7, and fecal samples were cultured for the bacteria. Three distinct patterns of shedding were observed: 1 month, 1 week, and 2 months or more. Similar patterns were confirmed among 29 forage-fed sheep and four cannulated steers. To identify the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
137
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 40 publications
13
137
2
Order By: Relevance
“…38,39 These initial studies centered on bovine ruminal phages, but more recent O157:H7 phage research has moved to the recto-anal junction, the demonstrated major site of colonization in cattle. 15,40 Much less is known about O157:H7 colonization in sheep but the data suggests that it attaches more widely, including in the colon and rectum. [41][42][43] During our studies we found that half of the members of a single sheep flock carried the same new O157:H7-infecting phage, CEV2.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 These initial studies centered on bovine ruminal phages, but more recent O157:H7 phage research has moved to the recto-anal junction, the demonstrated major site of colonization in cattle. 15,40 Much less is known about O157:H7 colonization in sheep but the data suggests that it attaches more widely, including in the colon and rectum. [41][42][43] During our studies we found that half of the members of a single sheep flock carried the same new O157:H7-infecting phage, CEV2.…”
Section: Resultsmentioning
confidence: 99%
“…This concern is directed to Salmonella spp. (24,27,40,47,49) and E. coli O157:H7, because cattle is its main reservoir, explaining the risk of transmission by manure (22,34,43,50).…”
Section: Discussionmentioning
confidence: 99%
“…Challenged older calves can have transient watery diarrhea or have no symptoms, as observed for mature cattle (Cray and Moon 1995;Brown et al 1997). EHEC O157:H7 has been isolated from the small and large intestine of older calves and mature cattle but not necessarily associated with A/E lesions (Cray and Moon 1995;Brown et al 1997;Grauke et al 2002;Naylor et al 2003;van Baale et al 2004). The current model for EHEC O157:H7 colonization in cattle suggests that the lymphoid-follicle dense mucosa in the terminal rectum is the primary colonization site and it is this colonization that is responsible for persistent shedding (Naylor et al 2003Sheng et al 2004Sheng et al , 2006Lim et al 2007).…”
mentioning
confidence: 99%